2014
DOI: 10.3390/s140610864
|View full text |Cite
|
Sign up to set email alerts
|

A New Surface Plasmon Resonance-Based Immunoassay for Rapid, Reproducible and Sensitive Quantification of Pentraxin-3 in Human Plasma

Abstract: A new immunoassay based on surface plasmon resonance (SPR) for the rapid, reproducible and sensitive determination of pentraxin-3 (PTX3) levels in human plasma has been developed and characterized. The method involves a 3-min flow of plasma over a sensor chip pre-coated with a monoclonal anti-PTX3 antibody (MNB4), followed by a 3-min flow of a polyclonal anti-PTX3 antibody (pAb), required for specific recognition of captured PTX3. The SPR signal generated with this secondary antibody linearly correlates with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The concentration of IL-6, IL-8 and VEGF in the cell culture medium was measured using the Quantikine ELISA assay (R&D Systems). The concentration of PTX3 both in the conditioned medium of ARPE-19 cells and in the vitreous humor of AMD and non-AMD donors was assessed using an in-house developed ELISA assay (Canovi et al, 2014).…”
Section: Enzyme-linked Immunosorbent Assaysmentioning
confidence: 99%
“…The concentration of IL-6, IL-8 and VEGF in the cell culture medium was measured using the Quantikine ELISA assay (R&D Systems). The concentration of PTX3 both in the conditioned medium of ARPE-19 cells and in the vitreous humor of AMD and non-AMD donors was assessed using an in-house developed ELISA assay (Canovi et al, 2014).…”
Section: Enzyme-linked Immunosorbent Assaysmentioning
confidence: 99%
“…Surface plasmon resonance (SPR) was recently shown to be a useful technique for estimating affinity of malaria-specific antibodies, using the dissociation constant (k d ) 21 . SPR has been recommended for use in vaccine efficacy studies to get more accurate evaluations 37 and it has also been shown to be suitable for use due to its efficiency in point-of-care diagnosis 38 , 39 . Antibody levels as determined by ELISA were also compared with SPR-measured affinity to further validate the use of SPR in measurement of affinity in malaria studies.…”
Section: Introductionmentioning
confidence: 99%
“…43 Though the detection of D-dimer in human plasma is more challenging than that in buffer samples, our sensor still exhibits a stable, sensitive performance.…”
Section: Detection Of D-dimer In Human Plasmamentioning
confidence: 98%